Stress-Induced Increases in the Levels of Caspases in the Prefrontal Cortex in a Rat Model of PTSD - Zhang, J.H.; Li, M.; Han, F.; Yu X. Shi (Нейрофизиология, 2016)
We investigated the levels of expression of caspase-3 and 9 in the medial prefrontal cortex
(mPFC) of rats subjected to single prolonged stress (SPS), trying to provide a novel insight
into the mechanism of how this cortical region is related to post-traumatic stress disorder
(PTSD). Fifty male Wistar rats were divided into the control group and four SPS groups
examined at days 1,4,7, and 14 after treatment. Expression of caspase-3 in SPS groups was
significantly greater when compared with the control group (P < 0.05) and peaked at day
7 after exposure to SPS. In the control group, the intensity of fluorescence of caspase-9-
positive cells was low, while that in the SPS groups was significantly higher (P < 0.01) and
peaked at day 4 after exposure to SPS. After SPS episodes, levels of mRNA of caspase-3 and
caspase-9, compared with those in the control group, gradually increased and peaked at days
7 and 4, respectively (P < 0.01). Therefore, changes of expression of caspase-9 and caspase-3
may play an important role in the pathogenesis of PTSD. Ми досліджували рівні експресії каспаз-3 та 9 у медіальній префронтальній корі (mPFC) щурів, підданих поодинокому епізоду тривалого стресу (SPS), намагаючись отримати нові дані щодо механізмів залучення цієї ділянки кори
в патогенез посттравматичного стресового розладу (PTSD).
50 самців щурів лінії Вістар були поділені на контрольну
групу та SPS-групи, досліджені через одну, чотири, сім та
14 діб після дії SPS. Експресія каспази-3 в групах SPS була
вірогідно посиленою порівняно з такою в контрольній групі
(P < 0.05), досягаючи найвищого рівня через сім діб після впливу SPS. У контрольній групі флуоресценція продуктів виявлення каспази-9 була слабкою, тоді як у групах SPS
вона була істотно сильнішою (P < 0.01); її рівень досягав
максимуму через чотири доби після дії SPS. Після епізодів
SPS рівні мРНК каспаз-3 та 9 поступово збільшувалися, досягаючи пікових значень на сьому та четверту добу відповідно (P < 0.01). Отже, зміни експресії каспази-3 та каспази-9 відіграють істотну роль у патогенезі PTSD.